The Influence of School Climate and Self-Efficacy on Students' Learning Motivation at SMP Negeri 2 Candi - Asma’ Islamiyah; Eko Hardi Ansyah (P3I UMSurabaya, 2024)
This study aims to determine the influence of School Climate and Self-Efficacy on Junior High School Students' Learning Motivation. This study uses an inferential quantitative method. The population in this study were junior high school students with a total of 280 respondents . Hypothesis testing using multiple linear regression assisted by data processing using SPSS version 20 For Windows . The hypothesis in this study can be accepted, namely there is an influence between school climate and self-efficacy on learning motivation of students of junior high school . The results of the study showed that the F value = 164.527 and the Sig value 0.000 < 0.05 . This means that there is a simultaneous influence between school climate and self-efficacy on learning motivation in students of SMP Negeri 2 Candi with an effective contribution of 54.3%, while the remaining 45.7% is influenced by other variables that have not been studied by researchers.